A primer in longitudinal data analysis - Taris, Toon (Online access: SAGE SAGE Research Methods Core., 2000)
Toon Taris' survival guide takes the reader through the strengths and weaknesses of longitudinal research, making clear how to design a longitudinal study, how to collect data most effectively and how to interpret results.